Vlachs in medieval Bulgaria in the research of Bulgarian scholars (20th–21st centuries) - Leszka, Mirosław; Marinow, Kirił (Balcanica Posnaniensia. Acta et studia, 2021)
The question of the place and role of the people referred in sources as Vlachs constitutes one of the most sensitive scientific problems. Sometimes they are influenced by contemporary nationalistic animosities. Most of the deliberations concerning this topic focus on the events connected to the restitution of Bulgarian statehood at the end of the 12th century, almost 170 years after its liquidation by the Byzantines. There are differences about the ethnic character of the leaders of the rebellion against the Byzantine power and its participants. The Bulgarian historiography of the 20th–21st century has developed two basic attitudes on the question of the meaning and role of the so-called Vlachs and Wallachia in the creation and history of the Second Bulgarian State. The first one is represented by scholars such as Vasil Zlatarski, Genoveva Cankova-Petkova, Borislav Primov, Nikolai Markov. They recognize the participation of ethnic Vlachs in the restitution of Bulgarian statehood. The second attitude (Petar Mutafchev, Ivan Dujchev, Ivan Bozhilov, Georgi Bakalov, Georgi Nikolov, Alexander Nikolov or Tervel Popov) completely negates their real presence among the insurgents or marginalizes it to the extreme. Moreover, none of the Bulgarian scholars are inclined to support the thesis popular among Romanian historians about the leading role of ethnic Vlachs in the restoration of the Bulgarian state at the end of the 12th century. Even the proponents of their real participation in this endeavor, including Primov, who is looking for a compromise formula, or Markov, who is clearly trying to present a fully objective view of the situation, either disagree with the hypothesis of the Wallachian lineage of the uprising’s leaders or choose not to formulate a clear conclusion on the matter. Of course, the views of scholars around each of these positions diverge in a number of details. On the other hand, all the historians in question (with one exception - Markov), hence, the representatives of both groups, share a rather similar argumentation, emphasizing the unquestionable Bulgarian character of both the driving forces behind the rebellion against the Byzantine power and the restored state. Most of this argumentation was formulated in the interwar period (Zlatarski, Mutafchev) and during the Second World War (Dujchev), and was later reproduced, and in some respects, slightly expanded by subsequent generations of historians.